Hubungan antara Regulasi Diri dengan Fear of Missing Out (FoMO) pada Mahasiswa Pengguna Media Sosial - Kusnadi, Melisa Lusiana; Suhartanto, Paulus Eddy (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2022)
This research aimed to determine the correlation between self-regulation and Fear of Missing Out (FoMO) in college students who used social media. The hypothesis of this research there was a negative correlation between self-regulation and Fear of Missing Out (FoMO) in college students who used social media. The participants of this research were 402 college students aged 18 to 25 years who used at least one of the following four social media: YouTube, WhatsApp, Facebook, or Instagram. This research was quantitative research using a non-probability sampling technique. The instruments used in this research were two scales arranged by the researcher, self-regulation modeled on Bandura’s self-regulation theory (in Feist et al., 2018), and the FoMO scale modeled on Przybylski et al’s FoMO theory (2013). According to the try-out of scales, the reliability coefficient on the self-regulation scale was 0,861 and on the FoMO scale was 0,815. The data analysis technique in this research used Spearman’s rho technique because the data were not normally distributed. The results of this research showed that there was a significant negative correlation between self-regulation and Fear of Missing Out (FoMO) in college students who use social media (r = -0,247, p = 0,000).